Will the Operation Britain Succeed? - Unknown (Evening News)
The Operation Britain Action Committee has organised "Operation Britain" which seeks assistance from the public in terms of funding to ensure that the Trinidad All Steel Percussion Orchestra (TASPO) leave Trinidad for the Festival of Britain in early July.
Keywords: Steel bands (Music) -- Trinidad and Tobago; Fund raising -- Trinidad and Tobago; Steel band music -- Trinidad and Tobago; Trinidad All Steel Percussion Orchestra -- History